Structured finance and insurance : - Culp, Christopher L. (Wiley, 2006)
Structured Finance and Insurance provides today's most detailed and well-grounded coverage of the latest alternatives for managing corporate risks by either employing insurance solutions or accessing capital markets. Case studies and examples help practitioners to understand that while insurance and financial solutions are in many ways similar, they often possess critical differences that can explode on the unwary user. By helping capital markets and insurance professionals to speak the same language—the common language of capital management and corporate finance—this essential book will bring structure and precision to an often-cloudy world and help eliminate the confusion that has, in the past, turned the convergence of structured finance and insurance from a financial boon to a headline-making nightmare.